2019
DOI: 10.1093/ajcn/nqy270
|View full text |Cite
|
Sign up to set email alerts
|

Dietary vitamin and carotenoid intake and risk of age-related cataract

Abstract: Background Existing studies suggest that dietary vitamins and carotenoids might be associated with a reduced risk of age-related cataract (ARC), although a quantitative summary of these associations is lacking. Objectives The aim of this study was to conduct a meta-analysis of randomized controlled trials (RCTs) and cohort studies of dietary vitamin and carotenoid intake and ARC risk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 49 publications
0
59
0
1
Order By: Relevance
“…Another study in Indians also suggested that consumption of vitamin C above 66.4 mg/day was less likely to have the cataract approximately 22%, compared to the individuals consuming vitamin C less than 10.8 mg/day [ 18 ]. Meta-analyses also confirmed such protective effect of vitamin C in Asian and US populations [ 19 ], and, in randomized controlled trials [ 6 ].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Another study in Indians also suggested that consumption of vitamin C above 66.4 mg/day was less likely to have the cataract approximately 22%, compared to the individuals consuming vitamin C less than 10.8 mg/day [ 18 ]. Meta-analyses also confirmed such protective effect of vitamin C in Asian and US populations [ 19 ], and, in randomized controlled trials [ 6 ].…”
Section: Discussionmentioning
confidence: 82%
“…A meta-analysis provided the comprehensive evidence that consuming sufficient amount of vitamin A reduced the risk of cataract by 17% (95% CI, 0.757–0.913) [ 4 ]. Another recent meta-analysis also reported the significantly reduced risk of cataract by the consumption of vitamin A and carotenoids: for vitamin A (relative risk [RR], 0.81; 95% CI, 0.71–0.92), and for beta-carotene (RR, 0.90; 95% CI, 0.83–0.99) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age-related cataract has also been associated with vitamin and carotenoid status [ 6 , 7 ]. Although nutrients such as vitamins A, C, and E, lutein, zeaxanthin, and β-carotene were associated with reduced cataract risk in cohort studies, inconsistent results are reported in RCTs [ 8 ]. Observational cohort studies suggest that regular consumption of nitrate-rich leafy green vegetables is associated with reduced risk of glaucoma development [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…eir vitamin A consumption does not meet the estimated average demand (EAR) or adequate intake (AI) of the Institute's dietary reference intakes (DRIs) [3]. Evidence from previous studies suggested that insufficient intake of vitamin A can cause numerous diseases, for example, HPV infection, obesity, and visual impairment [4][5][6]. erefore, the government tried to change the status of micronutrient deficiencies such as vitamin A through the enrichment and/or fortification (E/F) of food supply policy [7].…”
Section: Introductionmentioning
confidence: 99%